DAYA DUKUNG LINGKUNGAN HIDUP BERBASIS JASA EKOSISTEM PENYEDIA AIR DAN PANGAN DI KABUPATEN HULU SUNGAI UTARA - Rizkon, Muhammad; Kadir, Syarifuddin; Kissinger, Kissinger; Ridwan, Ichsan (EnviroScienteae, 2024)
The population growth in Hulu Sungai Utara District has led to an unsustainable exploitation of natural resources, negatively impacting environmental quality. This study aims to analyze the environmental support of ecosystem services, specifically focusing on water and food provision in the region. The analytical method involves calculating indicative environmental support based on ecosystem services. It includes the classification of ecoregion characteristics (landscapes and natural vegetation types), land cover assessment, and the creation of service/performance maps using the Simple Additive Weighting method. The results indicate a predominance of high to very high categories in the ecosystem service of water provision, covering 71.77% of the total area. Similarly, the ecosystem service of food provision is characterized by moderate to very high categories, with the moderate category covering 30.13%, the high category covering 36.32%, and the very high category comprising 24.83% of the total area in Hulu Sungai Utara District. These findings provide crucial insights for policymakers and local communities to formulate informed strategies and policies for sustainable water and food resource management.